Marketing and its impact on the sales of microenterprises in the commerce sector Guayas province period 2018 – 2022 - Zambrano Camacho, Nuria Raquel; Ochoa Reyes, Roberto David; Lovato Torres, Sofía Georgina (Revista Universidad de Guayaquil, 2024)
The objective of this research is to analyze marketing and its impact on the sales of microenterprises in the commerce sector in the province of Guayas. To achieve this, a theoretical compilation of the marketing strategies implemented was made, as well as a characterization of the microenterprises of the commercial sector of Ecuador, from which the challenges faced by these businesses in the period 2018 - 2022 can be considered. For this reason, a descriptive methodology was applied, with a quantitative approach and under a documentary review, sales data of microenterprises in the commercial sector were collected. From the analysis of the results, it was determined that, although these companies have increased their marketing expenditure in recent years, their sales have also grown, but have not achieved the desired takeoff. Some of the possible causes are related to the low budget allocated to advertising and marketing. Consequently, although there is marketing expenditure, especially in the digital field, it is still incipient and not very significant in the sales of microenterprises.
Keywords: Microenterprises; Commercial Sector; Marketing Strategies; Sales Management